Unpacking the Discursive Construction of Air Pollution in Official Chinese - Yao, Guangyuan (Círculo de Lingüística Aplicada a la Comunicación, 2025)
China has been grappling with an air pollution crisis for several years, causing significant impacts on public health and the environment. As the official English-language publication in China, China Daily serves as an essential medium for disseminating the Chinese government's messaging to the international community regarding environmental governance and policy. This study aims to examine the discourse on air pollution in the official English-language newspaper, China Daily, between 2016 and 2022. The research seeks to answer questions about how China Daily constructs the discourse on pollution, how it shapes public perception of China's environmental governance, and what sociopolitical factors influence China's response to environmental challenges. The study suggests that China's commitment to addressing environmental issues through policy measures and sound governance offers a promising outlook for a cleaner and sustainable future.